(untitled) (University Arena, 2025)
Complex function directly involved in the adjustment of individual behavior, psychomotricity provides the child with the optimal conditions for aquiring a system of skills designed to provide him with an effective adaptation to the growing demands of the environment in which he is active. Therefore, it is advisable to have a knowledge as thorough as possible, doubled with a clearer understanding of the main factors specific to the psychomotor phenomenon, the relationships established between them, their dynamics within the general motor component and their specific manifestation in certain environmental conditions (urban / rural). Present as a specific objective of physical education, the development of psychomotricity ensures the completion of the acquisitions specific to the various stages of learning in the life of the child. Knowing the level of development of the psychomotor component has always been a permanent concern of the specialists in the field of physical education, because it is the basis of the elaboration of the different intervention strategies, which are specific to each educational cycle, especially to every lesson of physical education. For this reason, the return of this age stage, of crucial importance for the further development of the child, to the research domain, is a well-defined goal of this research. Regarding the methods, 40 subjects, male and female primary school students, coming from urban and rural areas, were selected to participate in this research experiment. Using a part of the Bruininks-Oseretsky Test – Second Edition, the experiment analyzed possible differences between their psychomotor development, in the balance and strength subtests. The analysis of the results provided by this experiment allows specialists, directly involved in the educational process, to adapt it according to modern demands. Moreover, we can conclude that the use of Bruininks-Oseretsky Test - Second Edition (BOT-2), for the purpose of a thorough and complex psychomotor assessment of primary school students, is not only necessary but also advisable. The application of the physical education program at the level of the primary education cycle, by specialized teachers, is an essential condition for the professional guidance of the educational process and creates the opportunity to start some specific researches at this stage and to make a complete and complex evaluation of the different aspects related to the psychomotor behavior of the child.